ANALISIS ATAS PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA PERDATA NOMOR 304/PDT.G/2016/PN. BTM DITINJAU DARI ASAS ULTRA PETITA PETITUM PARTIUM DENGAN ADANYA TUNTUTAN SUBSIDAIR DALAM GUGATAN EX AEQUO ET BONO - Indra Kho; Ning Adiasih (Jurnal Hukum Adigama, 2021)
This study takes on the issue of the Judge's consideration in deciding a civil suitcase that is Ultra Petitum Partium in Decision Number: 304/Pdt.G/2016 /PN.Btm which has a subsidiary claim in a ex aequo et bono lawsuit. The type of research used is research for academic purposes. Approach of study is the statute approach. Literature study for the data collection technique; And with descriptive qualitative for the data analysis technique. The results show that with regard of judges' considerations in deciding civil suitcases, the ultra petitum partium in Decision Number: 304/PDT.G/2016/PN.Btm, with the subsidies claim in the ex aequo et bono lawsuit, which actually was in the Judge's civil suit, are prohibited to make a decision that exceeds what is demanded by the Plaintiff as regulated in Article 178 paragraph (3) Herziene Indonesisch Reglement and Article 189 paragraph (3) RBg. In the case of a decision made based on ex aequo et bono, it must not exceed the main material of the primair petitum, hence the decision passed respects ultra petitum partium and may not result in a loss to the defendant in defending his interests. However, in the Batam District Court Practice, namely in the case of decision number 304/pdt.G/2016/PN.Btm, the judge's consideration in deciding an ultra petitum partium civil suitcase was due to the existence of subsidiary demands based on the principles of justice and the judge's conviction to fulfil the rights of the plaintiff for the plaintiff is considered negligent to fulfil his justice.